Peningkatan Eksistensi Business Performance Umkm Kota Jambi dengan Model Entrepreneurial Marketing Strategy - Agustian, Efandri; Wuri Lastari, Adria; Mutiara, Indah (TIN: Terapan Informatika Nusantara, 2023)
The situation resulting from the Covid-19 Pandemic is a situation full of uncertainty (uncertainty). Some experts have even realized and predicted that a situation like this will have an impact and risk for economic actors, causing micro, small and medium enterprises (MSMEs) to be able to survive and compete to gain market share by implementing management strategies, concepts and management plans. . it is good. Using multiple linear regression analysis, it can be seen that the variables consumer orientation and innovation orientation have a significant influence on business performance. It is necessary to analyze the direct influence of entrepreneurial marketing dimensions on business performance so that the three independent variables do not have a direct influence on business performance. The purpose of this research is to formulate the ability to be able to utilize the resources they have even though they are limited (resource-based view) so that they can at least maintain financial performance or even be able to achieve competitive advantage with their competitors with the strategy being through the Entrepreneurial Marketing (EM) approach. The data in this research was obtained through distributing questionnaires and interviews with the Keys Coffee Shop manager in Jambi City. The research results show that the variables consumer orientation and innovation orientation have a significant positive influence on Coffee Shop business performance in Jambi City.